2008
DOI: 10.1002/polb.21642
|View full text |Cite
|
Sign up to set email alerts
|

Study of the assembled morphology of aryl amide derivative and its influence on the nonisothermal crystallizations of isotactic polypropylene

Abstract: The nonisothermal crystallization behaviors of isotactic polypropylene (iPP) with an aryl amide derivative TMB‐5 as β‐form nucleating agent has been investigated by differential scanning calorimetry, X‐ray diffraction, and polarized optical microscopy. The feature of crystallite morphology depends on concentration and thermal conditions. At low concentrations, TMB‐5 molecules aggregate into fibril structures and presented blunt exothermic peak with a shoulder at high temperature. The surface of these fibrils h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 51 publications
9
67
1
Order By: Relevance
“…Thus, the iPP/iPP‐5 samples had the highest density of the β‐form crystals in all of the samples at a cooling rate of 3°C/min. In the literature, it was shown that β‐form crystals could be formed under some special conditions, such as with the addition of a β‐nucleating agent, directional crystallization at certain temperature gradients, and shearing or elongation of the melt during crystallization . In our case, the nearby polymer chains were oriented by the transcrystalline crystallization of the polymer chains for the first.…”
Section: Resultsmentioning
confidence: 63%
“…Thus, the iPP/iPP‐5 samples had the highest density of the β‐form crystals in all of the samples at a cooling rate of 3°C/min. In the literature, it was shown that β‐form crystals could be formed under some special conditions, such as with the addition of a β‐nucleating agent, directional crystallization at certain temperature gradients, and shearing or elongation of the melt during crystallization . In our case, the nearby polymer chains were oriented by the transcrystalline crystallization of the polymer chains for the first.…”
Section: Resultsmentioning
confidence: 63%
“…The β-NA aryl amides derivative (trade name TMB-5, powder) with a melt temperature of 197°C was provided by Fine Chemicals Department of Shanxi Provincial Institute of Chemical Industry, China. It has been reported in the literatures that TMB-5 has chemical structure similar to N,N′-dicyclohexyl-2,6-naphthalene-dicarboxamide (commercial name NJS) [40,41].…”
Section: Methodsmentioning
confidence: 99%
“…However, up to now, the researchers mainly focus on the influence of the DS‐ β ‐NA (such as concentration) and the thermal conditions (fusion temperature, cooling rates, etc. ) and PP molecular weights . In the aspect of stereo‐defect distribution (tacticity distribution), the nucleating mechanism and influence of DS‐ β ‐NA on the dynamic crystallization and melting behavior of PP with different stereo‐defect distribution are still not clear as far as we concerned.…”
Section: Introductionmentioning
confidence: 91%